Estimation of Benefits and costs of Korea's unification: A critical Review. Issue 1 (30th April 2015) - Cheong, Inkyo
Abstract : Discussion of unification was for several decades focused on the costs rather than the benefits for Korea, until reports emphasizing the latter were published by Goldman Sachs (2009) and various Korean think tanks over the past four to five years. Although these studies can be evaluated positively in pointing out the benefits of unification rather than the concerns about the costs, several questions can be raised. This paper tries to evaluate the quality and credibility of existing studies and suggests a new approach for estimating the impact of unification. It proposes a computational general equilibrium (CGE) model to be based on the social accounting matrix (SAM) and input-output (IO) table for the North Korean economy, in order to produce more reliable estimates of the benefits and costs of unification and the impact of various cooperative activities between the two Koreas.